2016
DOI: 10.3126/jnarc.v1i0.15720
|View full text |Cite
|
Sign up to set email alerts
|

Wheat Yield Trend and Soil Fertility Status in Long Term Rice-Rice-Wheat Cropping System

Abstract: A long-term soil fertility experiment under rice-rice-wheat system was performed to evaluate the long term effects of inorganic fertilizer and manure applications on soil properties and grain yield of wheat. The experiment began since 1978 was laid out in randomized complete block design with 9 treatments replicated 3 times. From 1990 onwards, periodic modifications have been made in all the treatments splitting the plots in two equal halves of 4 x 3 m2 leaving one half as original. In the original treatments,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
(8 reference statements)
0
2
0
Order By: Relevance
“…The overall wheat grain yield increased after 16 year of experimentation compare to initial year. Rawal et al, (2015) observed that wheat grain yields were consistently higher in the NPK and FYM treatments than in treatments, where one or more nutrients were lacking. This result was also supported by Singh et al, (2017) who reported that highest productivity of wheat was recorded in the treatment comprising 100 % NPK + FYM in long term fertilizers experiment.…”
Section: Wheat Grain Yieldmentioning
confidence: 87%
“…The overall wheat grain yield increased after 16 year of experimentation compare to initial year. Rawal et al, (2015) observed that wheat grain yields were consistently higher in the NPK and FYM treatments than in treatments, where one or more nutrients were lacking. This result was also supported by Singh et al, (2017) who reported that highest productivity of wheat was recorded in the treatment comprising 100 % NPK + FYM in long term fertilizers experiment.…”
Section: Wheat Grain Yieldmentioning
confidence: 87%
“…While studying the wheat yield trend in longterm rice-wheat cropping system in silt loam soil of Bhairahawa (Nepal), Rawal et al, (2015) reported that yields were consistently higher in NPK and FYM treatments than the treatments where one or more nutrients were lacking. They concluded that the productivity of the wheat can be increased and sustained by supplementing the nutrient through the integrated long-term use of organic and inorganic source.…”
Section: Issn: 2319-7706 Volume 9 Number 1 (2020)mentioning
confidence: 99%